2019
DOI: 10.1002/app.48336
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated copolyimide membranes for sour mixed‐gas upgrading

Abstract: Three random and two block 4,4 0 -(hexafluoroisopropylidene)diphthalic anhydride (6FDA)-based copolyimides with different 6FpDA:Durene molar ratio varying from 25 to 80% were prepared and characterized. The pure-gas permeation data of their membranes were investigated at 100 psi and 22 C. The CO 2 /CH 4 ideal selectivity coefficient increased to around 47 with the increase of the 6FpDA content to 80% in the copolymer backbone while the CO 2 permeability coefficient found to be the highest (378 barrer) with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Chain rigidity could affect the chain packing density within the membrane matrix, which in turn might affect the membrane performance during gas separation . All measured T g values were greater than 360 °C, similar to the T g values of several polyimides studied previously in our group. ,,, …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Chain rigidity could affect the chain packing density within the membrane matrix, which in turn might affect the membrane performance during gas separation . All measured T g values were greater than 360 °C, similar to the T g values of several polyimides studied previously in our group. ,,, …”
Section: Resultssupporting
confidence: 82%
“…CO 2 permeability–CO 2 /CH 4 selectivity relationship chart depicting the pure-gas permeation performance of poly­(imide–oxadiazole) membranes compared to those of previously reported materials. Literature data refs .…”
Section: Resultsmentioning
confidence: 99%
“…(a) Column chart comparison of sour mixed-gas permeation performance of POz-CF 3 and FPT-Ph­(OH) membranes at 700 psi and 22 ° C. (b) Column chart comparison of sweet and sour mixed-gas permeation performance of POz-CF 3 and FPT-Ph­(OH) membranes at 500 psi and 22 ° C. (c) Sour mixed-gas plot to compare the H 2 S separation ability of prepared polymeric membranes to some reported membranes performances in the literature: CA, 6FDA-DAM, PIM-6FDA–OH, 6FDA-TPA­( t -Bu), TEG-6FDA-DAM:DABA (3:2), 6FDA-Durene/CARDO (1:3), 6FDA-Durene/MDEA (1:3), and 6FDA-6FpDA/6FDA-Durene (4:1) …”
Section: Results and Discussionmentioning
confidence: 99%
“…are limited by their modest performance. Compared to the massive works on CO 2 /CH 4 application, only few studies have aimed at the development of membrane materials for removal of natural sour gas components due to safety concerns and regulations when dealing with the highly toxic H 2 S. The aforementioned barriers made the literature for H 2 S removal studies extremely stingy and not reflecting the real aggressivity in terms of H 2 S percentage and feed pressure. …”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that the glassy 6FDA‐DAM polyimide membrane exhibited an even better H 2 S and CO 2 co‐removal efficiency than most reported rubbery polymer membranes under high pressure sour natural gas feeds (>46 bar). Recently, Hayek et al . have developed 6FDA‐based copolyimide membranes with different 6FpDA:Durene molar ratios and investigated their separation performance under sour natural gas feeds with different H 2 S concentrations.…”
Section: Introductionmentioning
confidence: 99%